Твір О. Гавроша «Музей пригод»: деякі зауваги до змісту і форми - Землянська, Аліна Вікторівна; Zemlianska, Alina; Устінова, Н. О.; Ustinova, N. O. (My University, 2025)
UA: У статті проаналізовано твір О. Гавроша з позиції особливостей сюжету й жанрово-стилістичної еклектики. Наголошено, що автор врахував основні тренди розвитку сучасної дитячої літератури, що робить художній текст цікавим для читачів, та сповненим освітньо-виховного впливу. /// EN: The article analyzes O. Gavrosh’s work from the perspective of the plot features and genre-stylistic eclecticism. It is emphasized that the author took into account the main trends in the development of modern children’s literature, which makes the literary text interesting for readers and has a significant educational impact.
Gavrosh’s work «Adventure Museum»: some notes on content and form
Keywords: жанрова еклектика; конспірологічний роман; детектив; фентезі; ефект «обманутого очікування»; genre eclecticism; conspiracy novel; detective; fantasy; the effect of «deceived expectation»